Genetic basis of Parkinson’s disease: inheritance, penetrance, and expression - Schulte, Claudia (Dove Medical Press, 2011)
Parkinson’s disease can be caused by rare familial genetic mutations, but in most cases it is likely to result from an interaction between multiple genetic and environmental risk factors. Over recent years, many variants in a growing number of genes involved in the pathogenesis of Parkinson’s disease have been identified. Mutations in several genes have been shown to cause familial parkinsonism. In this review, we discuss 12 of them (SNCA, LRRK2, Parkin, PINK1, DJ1, ATP13A2, PLA2G6, FBXO7, UCHL1, GIGYF2, HTRA2, and EIF4G1). Additionally, six genes have been shown conclusively to be risk factors for sporadic Parkinson’s disease, and are also discussed (GBA, MAPT, BST1, PARK16, GAK, and HLA). Many more genes and genetic loci have been suggested, but need confirmation. There is evidence that pathways involved in the rare familial forms also play a role in the sporadic form, and that the respective genes might also be risk factors for sporadic Parkinson’s disease. The identification of genes involved in the development of Parkinson’s disease will improve our understanding of the underlying molecular mechanisms, and will hopefully lead to new drug targets and treatment strategies.